The intersectionality of gender discrimination impact on Beth Harmon’s identity development in The Queen’s Gambit - Prasetyaningrum, Dyah Ayu; Ahdiani, Ulaya (Universitas Ahmad Dahlan, 2024)
The Queen's Gambit (2020) addresses gender inequality against women in male-dominated industries like chess. Queen's Gambit displays patriarchal structural and representational judgment of women. Gender discrimination affects women's careers, identities, and development. Thus, the study examines gender discrimination's intersectionality and its effects on Beth Harmon, a white low-class young woman. Pictures and talks from the series are the key data in this qualitative study. Also used are intersectionality theory to analyze gender discrimination statistics and stages of development theory to examine character identity development. Gender, age, ethnicity, class, prejudices, and appearances encountered by Beth Harmon shaped her multifaceted identity. Discrimination hindered Beth's development as a chess player and woman throughout her school years, adolescence, and young adulthood, leading to both dystonic and syntonic effects. Stereotypes and injustice give rise to discrimination; therefore, we must acknowledge various identities and histories to prevent a